Marine Fouling Characteristics of Biocomposites in a Coral Reef Ecosystem. (15th July 2021) - Contardi, Marco; Montano, Simone; Galli, Paolo; Mazzon, Giulia; Mah'd Moh'd Ayyoub, Amin; Seveso, Davide; Saliu, Francesco; Maggioni, Davide; Athanassiou, Athanassia; Bayer, Ilker S.
Abstract: Coral reefs are among the most diverse ecosystems in the world. The diversity of life found in the habitats created by corals is so large that the reefs are known as the "rainforests of the sea." Unfortunately, severe natural and anthropogenic changes such as ocean warming, acidification, coral diseases, and plastic pollution are extremely detrimental to this ecosystem. To enrich the ambient conditions of the corals and boost their growth, the potential of two biocomposites is evaluated based on biodegradable polyurethane and silicone matrices as scaffolds for the growth of oceanic organisms. Furthermore, their degradation is investigated within the coral reefs of Faafu Atoll, Republic of Maldives. The observations indicate that there are a significant number of organisms that settle and grow on these biocomposites in the Maldivian lagoon, both of an animal and photosynthetic nature. The biocomposites have the potential to become suitable scaffolds for diverse hard bottom fouling organisms. Moreover, the presence of coral larvae on the biocomposites suggests that during their biodegradation, these biocomposites can support the growth of organisms, generating a suitable environment for triggering the birth of new corals. Abstract : Two biodegradable biocomposites based on starch–polydimethylsiloxane and soybean lecithin‐wax‐polyurethane are fabricated and evaluated as scaffolds for the growth of oceanic organisms. Such materials placed underwater on the Maldivian lagoon for six months show biodegradation and the growth of several organisms, including coral larvae. Hence, the proposed biocomposites can represent a potential tool for supporting coral reef restoration.